2011
DOI: 10.1039/c1ee01782a
|View full text |Cite
|
Sign up to set email alerts
|

Voltage, stability and diffusion barrier differences between sodium-ion and lithium-ion intercalation materials

Abstract: To evaluate the potential of Na-ion batteries, we contrast in this work the difference between Na-ion and Li-ion based intercalation chemistries in terms of three key battery properties -voltage, phase stability and diffusion barriers. The compounds investigated comprise the layered AMO 2 and AMS 2 structures, the olivine and maricite AMPO 4 structures, and the NA-SICON A 3 V 2 (PO 4 ) 3 structures. The calculated Na voltages for the compounds investigated are 0.18-0.57 V lower than that of the corresponding L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
1,046
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,299 publications
(1,114 citation statements)
references
References 91 publications
45
1,046
1
5
Order By: Relevance
“…In this article, we performed a first-principles investigation of the phase stability and Na + ionic transport in undoped and M 4+ -doped (M = Si, Ge, and Sn) c-Na 3 PS 4 . We demonstrate that pristine c-Na 3 PS 4 is in fact an extremely poor ionic conductor, but with the introduction of Na + interstitials, a reasonably high conductivity can be achieved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this article, we performed a first-principles investigation of the phase stability and Na + ionic transport in undoped and M 4+ -doped (M = Si, Ge, and Sn) c-Na 3 PS 4 . We demonstrate that pristine c-Na 3 PS 4 is in fact an extremely poor ionic conductor, but with the introduction of Na + interstitials, a reasonably high conductivity can be achieved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, in layered structures, such as the AMO 2 cathode and graphite anode, 45,135 it is clear that the interlayer spacing has a substantial effect on the alkali migration barriers, whereas the relationship between alkali ion radii and bottleneck size seems to have a larger role in rigid close-packed anion frameworks (e.g., olivine LiMPO 4 ). 11 In addition to migration barriers, the concentration of carriers is another factor contributing to overall ionic conductivity. In this respect, experimental composition scanning is generally still a more rapid mean of determining optimal dopant concentrations because of the inherent difficulty in investigating small concentration changes using computational methods.…”
Section: Computational Studies Of Alkali Conduction Z Deng Et Almentioning
confidence: 99%
“…62 However, the maricite structure is uninteresting for battery applications given the lack of viable alkali diffusion pathways in the structure. Ong et al 11 previously performed a comparison of the alkali migration barriers in the olivine and layered structures using NEB calculations (Figure 7). They found that the Na migration barrier is slightly higher than the Li migration barrier in the olivine structure.…”
Section: Polyanion Oxidesmentioning
confidence: 99%
See 2 more Smart Citations